Implementation of Integrated Quality Management in Improving The Quality of Education At Madrasah Aliyah Raudlatul Ulum - Burhanudin, Moch Arif; Sumaryanto, Totok; Subagyo, Subagyo (Educational Management, 2018)
In recent years, there has been an increase in the number of students and achievements in both academic and non-academic fields. This happens allegedly because the agency has made management changes by applying TQM. The purpose of this research was to investigate: 1) application of TQM, 2) quality of school service. This research used descriptive qualitative research approach. This research was conducted in MA Raudlatul Ulum Guyangan Pati. The subject of research as a responsible source was the head of the madrasah. While the research informants were teachers, students, guardians, board members and madrasah committee. Data collection techniques are participant observation, interview, and documentation. The validity checks of the research data were obtained by triangulation of sources and methods. While data analysis techniques used interactive model analysis that includes: data collection, data reduction, data presentation, and conclusions. The results of the research can be summarized as follows: (1) Quality management system when viewed from TQM elements which include: (a) focus on the customer; (b) improvement on quality; (c) teamwork cooperation; have implemented quality management. (2) Improving the quality of school services is made by drawing up a strategic plan embodied in a development plan that contains the vision, mission and objectives and strategic programs of the school as well as the clear division of tasks. Learners are well served to start the learning process in the classroom or outside the classroom. For instance, by praying dhuha prayer, five-time prayers, and extracurricular activities. Thus the quality of the madrasah service is satisfactory.